Circulating Epstein-Barr virus DNA associated with hepatic impairment and its diagnostic and prognostic role in patients with gastric cancer - He, Hui-Chan; Han, Rui; Xu, Bo-Heng; Huang, Chan; Li, Min-Min; He, Cai-Yun; Lin, Wen-Qian (Frontiers in Medicine, 2022)
Epstein-Barr virus (EBV)-associated gastric cancer (EBVaGC) is a distinct subtype of gastric cancer (GC). However, little is known about the impact of this entity on its systematic incorporation in GC patients, and the utility of circulating EBV DNA in the management of GC remains uncertain. We recruited a total of 280 GC patients (113 EBVaGC and 167 EBV negative GC (EBVnGC)) and extracted the laboratory results by reviewing the medical record. With their archived tumor tissues and peripheral blood, we examined EBV presence using in situ hybridization of EBV-encoded small RNAs and real-time quantitative PCR of EBV DNA load, respectively. The EBV DNA, lymphocyte infiltration and CD8 were also assessed in tumor samples. In the presence of EBV infection, we found a significant rise in inflammatory biomarker CRP, liver enzymes ALP and GGT and coagulation indices PT and INR, and a decrease in albumin and albumin/globulin ratio (all P < 0.05). Circulating cell-free EBV DNA had positive correlations with the levels of GGT and tumor marker CA72-4 (P < 0.05). Both EBV DNA loads in tumor and in plasma were closely correlated with high-lymphocyte infiltration. High-lymphocyte infiltrated tumor tissues presented rich CD8+T cells. Of note, circulating cell-free EBV DNA demonstrate a predictive role in distinguishing EBVaGC from EBVnGC (AUC 0.79, 95% CI0.73 to 0.85, P < 0.001), and was associated with a better overall survival (HR 0.45, 95% CI 0.21 to 0.96, P = 0.039). These findings provided important hints of hepatic impairment and high inflammatory and immune response in EBV infected GC patients, and suggested circulating cell-free EBV DNA as an alternative diagnostic biomarker for EBV-related GC subtype, as well as an independent prognostic factor for the long-term survival benefit in GC patients.